2021
DOI: 10.3390/toxins13040283
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin in Dairy Cows: Toxicity, Occurrence in Feedstuffs and Milk and Dietary Mitigation Strategies

Abstract: Aflatoxins are poisonous carcinogens produced by fungi, mainly Aspergillus flavus and Aspergillus parasiticus. Aflatoxins can contaminate a variety of livestock feeds and cause enormous economic losses, estimated at between US$52.1 and US$1.68 billion annually for the U.S. corn industry alone. In addition, aflatoxin can be transferred from the diet to the milk of cows as aflatoxin M1 (AFM1), posing a significant human health hazard. In dairy cows, sheep and goats, chronic exposure to dietary aflatoxin can redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 118 publications
0
24
0
1
Order By: Relevance
“…The consumption of AF-contaminated food and feedstuff can lead to acute and chronic toxic effects whose gravity depends on various factors such as species, age, sex and exposure level. In livestock farming, AF-contaminated feed leads to a decrease in animal productivity, growth and final product quality, thus negatively impacting the whole supply chain [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of AF-contaminated food and feedstuff can lead to acute and chronic toxic effects whose gravity depends on various factors such as species, age, sex and exposure level. In livestock farming, AF-contaminated feed leads to a decrease in animal productivity, growth and final product quality, thus negatively impacting the whole supply chain [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bentonite is an adsorbent aluminosilicate clay consisting mostly of montmorillonite, commonly used as a feed additive to reduce AFs bioavailability (and, consequently, toxicity) in the gastrointestinal tract [ 18 , 21 , 22 ]. Experimental data show that AFM1 content in milk can be diminished by 60.4% when introducing 227 g bentonite/cow/day into cattle diet [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins are secondary metabolites produced by fungal species of the genus Aspergillus and other toxigenic strains of molds [ 1 ]. These compounds are associated with significant economic losses in agriculture, crop farming, and livestock activities [ 2 , 3 ], having an impact on 25% of the world’s crop harvest [ 4 , 5 ]. In addition, aflatoxins represent a serious hazard to food safety because of their worldwide distribution and high carcinogenicity, among which aflatoxin B1 (AFB1) is the most harmful type and responsible for the greatest economic and health burden worldwide [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many surveys about AFB 1 contamination in feedstuffs have been done worldwide, the overall data showed that most of the AFB 1 risk in the dairy feed is low and moderate levels [13,[24][25][26]. Biomin Inc. (Ferndale, MI, USA) conducted a worldwide survey of mycotoxin contamination in feed ingredients in 2018 [27] and 2019 [28], the results showed that the aflatoxin positive rates of finished feed in Asia were 44% and 30%, respectively, and the median of positive samples were both 8 µg/kg [29]. Meanwhile, most researchers conducted the field trails in a critical high level of (>20 µg/kg) AFB 1 dosages from 20 µg/kg [19,30,31], 22.28 µg/kg (naturally contaminated) [32], 40 µg/kg [31], 63 µg/kg [17], 76 µg/kg (1725 µg/d) [33], 100 µg/kg [34,35], 120 µg/kg [36] and up to 300 µg/kg in diet to investigate their negative effects to the cows [34].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous epidemiological surveys on AFM 1 in commercial and raw milk have assessed their exposure risk for humans, data on AFB 1 content in the diets were usually unusable. Meanwhile, when the prevention of aflatoxin contamination with crops and grains during pre-harvest and storage fails, adding AFB 1 adsorbents to dairy diets was proved to be a very effective option to mitigate the negative impact of AFB 1 [29]. However, few studies have determined the effects of moderate risk AFB 1 and adsorbents in the diet on production performance and milk AFM 1 concentration of lactating dairy cows and the risk assessment of milk AFM 1 residual for different populations, although most of the dairy cows are likely facing moderate risk AFB 1 exposure every day.…”
Section: Introductionmentioning
confidence: 99%